1984
DOI: 10.1007/bf01296271
|View full text |Cite
|
Sign up to set email alerts
|

Influence of meal weight and caloric content on gastric emptying of meals in man

Abstract: This study was designed to assess the relative influence of meal weight and caloric content on gastric emptying of liquid and solid meals in man. A dual radioisotopic method which permits noninvasive and simultaneous measurement of liquid- and solid-phase emptying by external gamma camera techniques was employed. Nine healthy volunteer subjects ingested 50-, 300-, and 900-g lettuce and water meals adjusted to either 68, 208, or 633 kcal with added salad oil. The following observations were made: (1) absolute e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 10 publications
5
43
1
Order By: Relevance
“…Increasing the volume will speed emptying, but increasing the nutrient content will slow emptying. 17,18 Osmolality, temperature, and pH of drinks are of minor importance. 17,18 It should also be noted that gastric emptying time is a variable phenomenon in healthy subjects with significant inter-and intraindividual day-to-day differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the volume will speed emptying, but increasing the nutrient content will slow emptying. 17,18 Osmolality, temperature, and pH of drinks are of minor importance. 17,18 It should also be noted that gastric emptying time is a variable phenomenon in healthy subjects with significant inter-and intraindividual day-to-day differences.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Osmolality, temperature, and pH of drinks are of minor importance. 17,18 It should also be noted that gastric emptying time is a variable phenomenon in healthy subjects with significant inter-and intraindividual day-to-day differences. 19 Our results have also shown that patients in the apple juice group experienced more thirst and hunger than those in the control and water groups (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…So we discussed the transfer process in relation to the gastric emptying. Concerning gastric emptying, it is known that when the contents of the stomach are in a liquid state, the contents are emptied out generally with the first-order rate process (2,7,8). Therefore, we first analyzed the concentrations in plasma according to equation 1, which was derived from the model assumed to have a first-order transfer process.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, cocoa may alleviate the effects of lactose in milk chocolate. Since solid consistency and high energy content of food delays gastric emptying (Moore et al, 1984;Notivol et al, 1984;Marciani et al, 2001), lactose eaten in milk chocolate may even induce fewer symptoms than the respective amount of lactose in chocolate milk. It has been previously demonstrated that consuming milk or lactose with a meal or other foods produces less breath hydrogen and gastrointestinal symptoms (Solomons et al, 1985;Martini & Savaiano, 1988;Dehkordi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%